Formal aspects of component software : 11th International Symposium, FACS 2014, Bertinoro, Italy, September 10-12, 2014, Revised selected papers /: 11th International Symposium, FACS 2014, Bertinoro, Italy, September 10-12, 2014, Revised selected papers. ([2015]) - Unknown
No abstract available